Carbon Dioxide Capture Properties of MgCl2 Templated Microporous Carbon from p-toluenesulfonic Acid - Zaman, Ali Can (GAZI UNIV, 2022)
Herein, porous carbon materials were prepared using p-toluenesulfonic acid (TsOH) as a carbon source with (TsOH-STC) and without (TsOH-C) presence of MgCl2 center dot 6H(2)O. The products were evaluated in terms of CO2 (carbon dioxide) adsorption performance, texture and surface chemical structure. Both samples contain oxidized sulfur on their surface according to X-ray photoelectron spectroscopy (XPS). TsOH-STC has a 3D porous network, but TsOH-C consists of a dense structure. It was understood that TsOH-C is not suitable to be analyzed with N-2 adsorption at cryogenic temperatures probably due to restricted access to narrow pores due to lack of external surface. The CO2 uptakes are 0.78 mmol g(-1) for TsOH-C and 0.67 mmol g(-1) for TsOH-STC at flue gas conditions (0.15 bar and 298 K) of coal fired power plants, which is a projection of ultramicropore (pores smaller than 0.7 nm) volume in 0.5 nm range. TsOH-C has CO2 uptake capacity of 2.21 mmol g(-1) and TsOH-STC reaches 2.47 mmol g(-1) at 1 bar at 298 K. Maximum CO2 adsorption enthalpy (Q(st)) value for TsOH-C is 24.9 kJ mol(-1) and that of TsOH-STC is 25.7 kJ mol(-1). IAST (ideal adsorbed solution theory) selectivities (CO2:N-2 = 15:85) of the samples are 13.5 for TsOH-STC and 19.7 for TsOH-C at 1 bar. It was shown in this study that salt templating with MgCl2 does not influence ultramicroporosity development and provide moderate level CO2 capture performance. However, templating induces formation of supermicropores (micropores larger than 0.7 nm), large mesopores and macropores on TsOH derived carbons.
Keywords: CO2 capture; Microporous carbon; Sulfur doped carbon; Physisorption; CO2 ADSORPTION; POROUS CARBONS; SURFACE-CHEMISTRY; ACTIVATED CARBON; DOPED CARBONS; NITROGEN; GAS; DYE; Science & Technology - Other Topics